2013
DOI: 10.4236/aim.2013.36063
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Urinary Tract Infections and Its Aetiological Agents among Pregnant Women in Karnataka Region

Abstract: Urinary tract infection (UTI) is the most common medical complications of pregnancy together with anaemia and hypertension and it occurs approximately in 5%-10% of all pregnancies. The aim of this study was to determine the incidence of UTI and prevalence of uropathogens among pregnant women. During the study period from December 2009 to August 2010, 417 urine samples were analyzed. UTI was diagnosed by growth of at least 10 5 CFU/ml of a urinary tract pathogen in a culture of a midstream urine sample. The iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
5
14
1
Order By: Relevance
“…In the current study, a 45% positive culture rate was reported, this is a higher rate than those obtained from previous studies carried out by different researchers in the same governorate (Dimetry et al, 2007), the prevalence of laboratory confirmed UTI in pregnant was estimated to be 30.29% in neighboring regions (Suez governorate) in Egypt (Mohamed et al, 2017). Similar findings were obtained in Yemen and Bangaldish (Almushait et al, 2013), however Indian (Manjula et al, 2013) and Nigerian (Onoh et al, 2013) studies reported slightly raised rates (49.4% and 46.5% respectively). This variation may be explained by the differences in characteristics of study populations, environmental conditions and methodology.…”
Section: Discussionsupporting
confidence: 78%
“…In the current study, a 45% positive culture rate was reported, this is a higher rate than those obtained from previous studies carried out by different researchers in the same governorate (Dimetry et al, 2007), the prevalence of laboratory confirmed UTI in pregnant was estimated to be 30.29% in neighboring regions (Suez governorate) in Egypt (Mohamed et al, 2017). Similar findings were obtained in Yemen and Bangaldish (Almushait et al, 2013), however Indian (Manjula et al, 2013) and Nigerian (Onoh et al, 2013) studies reported slightly raised rates (49.4% and 46.5% respectively). This variation may be explained by the differences in characteristics of study populations, environmental conditions and methodology.…”
Section: Discussionsupporting
confidence: 78%
“…This is similar to the findings reported by Abid et al (2013) among pregnant patients with UTIs in Pakistan but higher than the percentages (49.4%) reported in earlier studies by Manjula et al (2013) in pregnant patients in India and 30% by Tamalli et al (2013) in pregnant women who were followed up at different antenatal care clinic in Libya. The high prevalence of UTIs may be explained by sexual intercourse and pregnancy due to the normal physiologic changes induced by gestation which render pregnant women especially susceptible to these infections (National Institutes of Health, 2004;Kolawole et al, 2009).…”
Section: Discussionsupporting
confidence: 63%
“…Prevalence of UPEC in this study is higher than earlier report in India where E. coli (56.79%) predominates the pathogens recovered (Manjula et al, 2013), and 43.27% reported by Ehsan et al (2013) as the most prevalent among pregnant women. The recovery of only species of E. coli from 226 of the patients suggests a mono-microbial nature of E. coli in UTIs.…”
Section: Discussioncontrasting
confidence: 55%
“…[9] [22] [28] also noted in their studies that E. coli was the most commonly isolated pathogen in significant bacteriuria. In a similar study by [29], E. coli was found to be the most implicating pathogen.…”
Section: Discussionmentioning
confidence: 78%